Statin Use and Outcomes of Patients With Acute Ischemic Stroke Treated With Intravenous Thrombolysis: A Systematic Review and Meta-Analysis - Guo, Yu; Guo, Xinmei; Zhao, Kai; Bao, Qiangji; Yang, Jincai; Yang, Mingfei (Frontiers in Neurology, 2021)
Background: The data on the relationship between statin use and clinical outcomes after intravenous thrombolysis (IVT) for acute ischemic stroke (AIS) are in controversy. Objective: This systematic review and meta-analysis aimed to evaluate the safety and efficacy of statins administered prior to onset and during hospitalization in patients with AIS treated with IVT. Methods: We searched PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials from inception until June 8, 2021. Comparative studies investigating statin effect on intracranial hemorrhage (ICH), functional outcomes, and mortality in adults with AIS treated with IVT were screened. Random-effect meta-analyses of odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were performed. The protocol was registered in PROSPERO (CRD42021254919). Results: Twenty-two observational studies were included, which involved 17,554 patients. The pooled estimates showed that pre-stroke statin use was associated with a higher likelihood of symptomatic ICH (OR 1.31; 95% CI 1.07–1.59; p = 0.008) and any ICH (OR 1.21; 95% CI 1.03–1.43; p = 0.02). However, the pre-stroke statin use was not significantly associated with the 3-month mortality, 3-month favorable functional outcome (FFO, modified Rankin Scale [mRS] score 0–1), and 3-month functional independence (FI; mRS score 0–2). However, in-hospital statin use was associated with a reduced risk of symptomatic ICH (OR 0.46; 95% CI 0.21–1.00; p = 0.045), any ICH (OR 0.51; 95% CI 0.27–0.98; p = 0.04), and 3-month mortality (OR 0.42; 95% CI 0.29–0.62; p < 0.001) and an increased probability of 3-month FFO (OR 1.33; 95% CI 1.02–1.744; p = 0.04) and 3-month FI (OR 1.41; 95% C, 1.11–1.80; p = 0.005). Conclusions: The present systematic review and meta-analysis suggests that in-hospital statin use after IVT may be safe and may have a favorable impact on clinical outcomes, a finding not observed in studies restricted to patients with pre-stroke statin use.